Carbon Coated MoO3 Nanowires/Graphene oxide Ternary Nanocomposite for High-Performance Supercapacitors. (20th November 2016) - Shaheen, Wajeeha; Warsi, Muhammad Farooq; Shahid, Muhammad; Khan, Muhammad Azhar; Asghar, M.; Ali, Zahid; Sarfraz, Mansoor; Anwar, Hafeez; Nadeem, Muhammad; Shakir, Imran
Graphical abstract: A novel ternary nanocomposite of rGO/MoO3 @C nanowires was synthesized by facile bottom up approach. These nanocomposites exhibited the high electrical conductivity, high specific capacitance and excellent cyclic stability. Highlights: A novel ternary nanocomposite of rGO/MoO3 @C nanowires was synthesized. The novel rGO/MoO3 @C nanowires exhibited high conductivity and high capacittance. The ternary nanocomposite show potential for next-generation energy storage devices. Abstract: A ternary nanocomposite of molybdenum trioxide (α-MoO3 ) nanowires coated with a thin layer of carbon, which is intertwined with graphene oxide is synthesized by hydrothermal and ultrasonication route. It is found that high conductivity of carbon coated MoO3 nanowires is further increased by introducing the graphene sheets. The ternary nanocomposite (rGO/MoO3 @C) exhibits high specific capacitance, excellent cyclic stability compared to the carbon coated MoO3 (MoO3 @C) and virginal MoO3 nanowires due to the synergistic effect of carbon layer and graphene. The electrochemical impedance measurements show that rGO/MoO3 @C nanocomposite have lower charge transfer resistance as compared to MoO3 @C and MoO3 nanowires electrodes. Two probe electrical conductivity ( I–V ) measurements confirm the enhanced conductivity of rGO/MoO3 @C nanocomposite relative to MoO3 @C and bare MoO3 nanowires. The electrical and electrochemical measurements indicate that the rGO/MoO3 @C nanocomposite is promising candidate for energy storage applications.